Working girl [videorecording (DVD)] - Nichols, Mike; Wade, Kevin; Griffith, Melanie, 1957-; Weaver, Sigourney, 1949-; Ford, Harrison, 1942-; Spacey, Kevin (20th Century Fox, 2009)
A secretary with a head for business takes advantage of her boss's bed-ridden condition and arranges a business deal. This title has been Repackaged.